2018
DOI: 10.5888/pcd15.180326
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of a Park-Based Physical Activity Program on Cardiovascular, Strength, and Mobility Outcomes Among a Sample of Racially/Ethnically Diverse Adults Aged 55 or Older

Abstract: IntroductionMany older adults are not physically active despite the well-documented health benefits of regular exercise. We examined cardiovascular, strength, and mobility outcomes among a sample of racially/ethnically diverse adults aged 55 or older participating in a community park-based physical activity program. MethodsWe assessed the following among adults aged 55 or older who attended a 1-hour park-based fitness class 2 or 3 times per week for 21 weeks: 1) 3 fitness outcomes, 2) systolic and diastolic bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 17 publications
0
7
0
2
Order By: Relevance
“…Sixteen studies were RCTs ( Bail et al, 2018 ; Bay-Richter et al, 2012 ; Bielinis et al, 2021 ; Brown et al, 2014 , Brown et al, 2020 ; Calogiuri et al, 2016 ; Gidlow et al, 2016 ; Han et al, 2018 ; Martens et al, 2011 ; Müller-Riemenschneider et al, 2020 ; Ng et al, 2018 ; Olafsdottir et al, 2020 ; Song et al, 2015 , 2018 ; Van Den Berg et al, 2011 ; Vujcic et al, 2017 ); eighteen studies (19 papers) were controlled studies ( Bang et al, 2017 ; Barton et al, 2010 ; Berman et al, 2012 ; de Brito et al, 2019 ; Gerber et al, 2017 ; Hawkins et al, 2015 ; Holt et al, 2019 ; Johansson et al, 2011 ; Lanki et al, 2017 ; Lee et al, 2011 , Lee et al, 2014 ; Lucke et al, 2019 ; Lyu et al, 2019 ; Marselle et al, 2013 ; Oh et al, 2018 ; Sin-Ae et al, 2016 , 2017 ; Yao et al, 2017 ; Zeng et al, 2020 ); and sixteen studies were single group before and after designs ( Bettmann et al, 2017 ; Coventry et al, 2019 ; Furuyashiki et al, 2019 ; Gonzalez et al, 2011 ; Hall et al, 2018 ; Iwata et al, 2016 ; Kling et al, 2018 ; Korpela et al, 2016 ; Mackay et al, 2010 ; Marselle et al, 2016 ; McCaffrey et al, 2016 ; Mourão et al, 2019 ; Warber et al, 2015 ; Wilson et al, 2011 ; Wood et al, 2016 ; Wyles et al, 2017 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sixteen studies were RCTs ( Bail et al, 2018 ; Bay-Richter et al, 2012 ; Bielinis et al, 2021 ; Brown et al, 2014 , Brown et al, 2020 ; Calogiuri et al, 2016 ; Gidlow et al, 2016 ; Han et al, 2018 ; Martens et al, 2011 ; Müller-Riemenschneider et al, 2020 ; Ng et al, 2018 ; Olafsdottir et al, 2020 ; Song et al, 2015 , 2018 ; Van Den Berg et al, 2011 ; Vujcic et al, 2017 ); eighteen studies (19 papers) were controlled studies ( Bang et al, 2017 ; Barton et al, 2010 ; Berman et al, 2012 ; de Brito et al, 2019 ; Gerber et al, 2017 ; Hawkins et al, 2015 ; Holt et al, 2019 ; Johansson et al, 2011 ; Lanki et al, 2017 ; Lee et al, 2011 , Lee et al, 2014 ; Lucke et al, 2019 ; Lyu et al, 2019 ; Marselle et al, 2013 ; Oh et al, 2018 ; Sin-Ae et al, 2016 , 2017 ; Yao et al, 2017 ; Zeng et al, 2020 ); and sixteen studies were single group before and after designs ( Bettmann et al, 2017 ; Coventry et al, 2019 ; Furuyashiki et al, 2019 ; Gonzalez et al, 2011 ; Hall et al, 2018 ; Iwata et al, 2016 ; Kling et al, 2018 ; Korpela et al, 2016 ; Mackay et al, 2010 ; Marselle et al, 2016 ; McCaffrey et al, 2016 ; Mourão et al, 2019 ; Warber et al, 2015 ; Wilson et al, 2011 ; Wood et al, 2016 ; Wyles et al, 2017 ).…”
Section: Resultsmentioning
confidence: 99%
“…Over half of the studies were conducted in Europe (n=25); fourteen in Asia; ten in North America; and one in Australia. Samples in 24 studies were drawn from healthy adult non-clinical populations ( Bielinis et al, 2021 ; Brown et al, 2014 ; Calogiuri et al, 2016 ; de Brito et al, 2019 ; Furuyashiki et al, 2019 ; Gerber et al, 2017 ; Gidlow et al, 2016 ; Hawkins et al, 2015 ; Kling et al, 2018 ; Lanki et al, 2017 ; Lee et al, 2014 ; Lucke et al, 2019 ; Mackay et al, 2010 ; Marselle et al, 2013 , Marselle et al, 2016 ; McCaffrey et al, 2016 ; Mourão et al, 2019 ; Müller-Riemenschneider et al, 2020 ; Ng et al, 2018 ; Sin-Ae et al, 2017 ; Song et al, 2018 ; Van Den Berg et al, 2011 ; Warber et al, 2015 ). Eight studies recruited university student volunteers ( Bang et al, 2017 ; Han et al, 2018 ; Holt et al, 2019 ; Lee et al, 2011 ; Olafsdottir et al, 2020 ; Zeng et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…exercise classes, organized hikes, walking tours). It is possible that women are more likely to utilize this type of service and thus benefit at a higher level than the male population, with the demographic make-up of two recent studies suggesting this may be the case (Han et al, 2015; Kling, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…An intervention including individualized prescription of PA and limited supervision of execution may address these necessities. Additionally, walking may be an ideal modality because of its easy execution and low cost and risk (10). Previous studies showed that supervised PA in public places (11) and unsupervised programs conducted under experimental conditions (12) promote health benefits.…”
Section: Introductionmentioning
confidence: 99%